Histological Evaluation of Gastric Mucosa in Individuals with Gastric Ulcers and Its Association with Kidney Function - Hamid, Ruqayya Saad; Raghad Hazem Alabbasy; Azhar Khalaf Alazzawi (Indonesian Journal on Health Science and Medicine, 2025)
Gastric ulcers remain a major gastrointestinal disorder with significant global morbidity, frequently linked to hematological disturbances and systemic complications. While Helicobacter pylori infection and non-steroidal anti-inflammatory drug (NSAID) use are the leading causes of gastric ulcers, less attention has been given to their systemic impact, particularly on renal function and hematological status. Limited studies have explored the combined histological, hematological, and renal alterations in gastric ulcer patients, especially in developing regions. This study aimed to evaluate gastric mucosal histopathology in ulcer patients and investigate its association with hemoglobin levels, packed cell volume, and kidney function. Ninety participants were studied, including 60 with gastric ulcers and 30 controls. Patients demonstrated significantly reduced hemoglobin (11.55 ± 2.31 g/dL) and packed cell volume (36.37 ± 7.51%) compared with controls (p ≤ 0.05). Kidney function analysis revealed elevated urea (32.93 ± 9.41 mg/dL) and creatinine (0.816 ± 0.205 mg/dL) in patients versus controls (p ≤ 0.05). Histological examination of 100 gastric biopsies showed inflammation in 93% of cases, with active chronic inflammation in 59%, and H. pylori infection in 66% of samples. This is one of the first studies in Iraq to link histological gastric ulcer findings with both hematological parameters and renal function, providing an integrative view of disease impact. The findings highlight the need for comprehensive management of gastric ulcer patients, including regular monitoring of hematological and renal markers, alongside histopathological evaluation, to prevent systemic complications and improve outcomes. Highlights: Gastric ulcer patients showed significantly lower hemoglobin and packed cell volume compared to healthy controls. Kidney function was impaired in gastric ulcer patients, with elevated urea and creatinine levels. Histological analysis revealed high prevalence of chronic inflammation (93%) and Helicobacter pylori infection (66%) in gastric ulcer tissues.